(untitled) (diségno, 2024)
The research, which is part of the larger PNRR project PE5 – CHANGES – SPOKE 1 – HISTORICAL LANDSCAPES, aims to develop a comprehensive strategy for the knowledge and enhancement of the Phlegraean Fields, an area that, being subject to numerous and incessant geological, natural and anthropogenic events, is now characterized by a high degree of physical, cognitive and symbolic fragility. Starting from the paintings that have as their subject the Phlegrean landscape, the research develops some specific thematic paths based on distinguishing and identitarian aspects of the Phlegrean territory, to encourage a rediscovery of stories, values and meanings inherent in it. Taking advantage of new GIS-based technologies, such as ESRI’s StoryMaps, a new digital narrative was constructed in which landscape paintings, without a necessary chronological line, have been intertwined according to a common narrative matrix and then narrated through descriptive texts, multimedia content and interactive maps. In the maps, in particular, the geolocated paintings become the stages of a digital thematic itinerary that the user can take by assuming the same point of view used by the artists in the landscape views they painted. In this way, we aim both to bring to light the communicative value of such paintings, repositories of different landscape values, and to build new relationships between representations and real places, making the contemporary Phlegrean landscape more readable, or better intelligible.